Biodegradable and Water Resistant Poly(vinyl) Alcohol (PVA)/Starch (ST)/Glycerol (GL)/Halloysite Nanotube (HNT) Nanocomposite Films for Sustainable Food Packaging - Abdullah, Zainab Waheed; Dong, Yu (Frontiers in Materials, 2019)
As a novel biodegradable material, poly (vinyl) alcohol (PVA)/starch (ST)/ glycerol (GL)/ halloysite nanotube (HNT) nanocomposite films were prepared by solution casting at the HNT contents of 0.25, 0.5, 1, 3, and 5 wt%. Water absorption capacity and water solubility of nanocomposite films were decreased remarkably by 44.24 and 48.05%, respectively, with increasing the HNT content from 0 to 5 wt% when compared with those of biopolymer matrices. Moreover, the water contact angle of nanocomposite films increased by 21.36° with the incorporation of HNTs. The presence of HNTs appeared to reduce the overall migration rates for PVA/ST/GL/HNT nanocomposite films when interacting with either hydrophilic or lipophilic food simulants. However, the migration rates of HNTs alone were enhanced with increasing the HNT content in hydrophilic, lipophilic, and acidic food simulants. On the other hand, the biodegradation rate and light transmittance of nanocomposite films were reduced linearly by 18.56 and 26.90% with increasing the HNT content from 0 to 5 wt%. Overall, novel PVA/ST/GL/HNT nanocomposite films in this study offer highly competitive materials with excellent water resistance, good biodegradability, and acceptable transparency to be potentially used for sustainable food packaging particularly targeting lipophilic and acidic foodstuffs.